Negócios jurídicos processuais e direito probatório: uma análise dos limites convencionais no processo civil - Cheida, Daniel Souto (2023)
The purpose of the work, presented here, is to reflect the limits that the parties must observe in carrying out procedural legal transactions in the current system of the Code of Civil Procedure, which values communication between the parties involved in the process; freedom of choice; a cooperation. The object of study is to examine the landmarks in procedural legal transactions involving evidentiary law, which cannot be done without seeking to understand the concepts behind the theory of procedural legal transactions and their respective limits, as well as the main notions of proof and convincing. In terms of structure, the study is divided into three parts. The first addresses the theory of the legal fact as a predictive element of the norm and how they influence procedural legal facts, so that it is possible to apply the concept of procedural legal business as capable of producing effects in the process, its evolution over time, its classification, limits, general and specific conditions of validity, effectiveness and existence. In the second part, it enters into the general notions of evidence in the Brazilian legal system. Finally, it analyzes the evidentiary procedural conventions and their respective limits.